Comparison between the sponge fauna living outside and inside the coralligenous bioconstruction. A quantitative approach - CALCINAI, B.; BERTOLINO, M.; BAVESTRELLO, G.; MONTORI, S.; MORI, M.; PICA, D.; VALISANO, L.; CERRANO, C. (Mediterranean Marine Science, 2015)
Coralligenous habitat results from a multi-stratified accumulation of crustose coralline algae and animal builders in a dynamic equilibrium with disruptive agents. The result is a complex architecture crossed by crevices and holes. Due to this three-dimensional structure, coralligenous may host a rich and diversified fauna, more abundant than any other Mediterranean habitat. Unfortunately, very few data are available about the cryptic fauna that lives inside the conglomerate. As already reported for coral reefs, the cryptic fauna plays an important role in the exchange of material and energy between water column and benthic assemblages. Here we compare the sponge community present inside and outside the coralligenous framework of Portofino Promontory (Ligurian Sea) at different depths (15 and 30 meters) not only in terms of taxonomic diversity but for the first time also in term of biomass. Sponges present on the surface of each block were collected, weighed and identified; after blocks dissolution in HCl, target cryptic sponges were separated from other organisms, weighed, and identified. We recorded a total of 62 sponge species. The average number of sponge taxa occurring outside the coralligenous accretions is lower than the number of taxa identified inside. This pattern is confirmed also regarding sponge biomass. These results underlines that studies focused on coralligenous functioning should take in account the important contribution of cryptic fauna, as recently evidenced also for tropical reef habitats.